Revelation, Gender, and the ‘Brooten Phenomenon’ - Huber, Lynn (Journal for the study of the New Testament, 2025)
Drawing inspiration from Sara Parks’s article on the ‘Brooten Phenomenon’, which references Bernadette J. Brooten’s groundbreaking work on women’s lives in the ancient world, this article addresses the tendency to overlook scholarship on Revelation by women and about gender. The article offers close analyses of recent commentaries and articles on Revelation and finds that women’s scholarship is cited mainly when discussing gender and often relegated to footnotes. This lack of citation belies the significant presence of women-identified scholars publishing on Revelation.